Pulmonary vasculitis in Behçet’s disease: reference atlas computed tomography pulmonary angiography (CTPA) findings and risk assessment-management proposal - Emad, Yasser; Ragab, Yasser; Cozzi, Diletta; Ibrahim, Ossama; Abdelrahman, Walaa; Abdelali, Mabrouk; Kechida, Melek; Hassanin, Manal; Tharwat, Samar; Salah, Shaimaa; Elshaarawy, Nashwa; Frikha, Faten; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim.  Pulmonary artery aneurysms (PAAs) are the most well-defined type of pulmonary vascular complication in Behçet's disease (BD).The aim of this study is to analyze which CT pulmonary angiography (CTPA) signs are associated with serious morbidity and mortality.Methods. The study included 42 BD patients with pulmonary vascular complications. All patients' medical records were reviewed retrospectively in terms of demographics, disease characteristics, laboratory investigations, pulmonary manifestations, arterial and/or venous thrombosis and CTPA vascular and parenchymal findings.Results. Deep venous thrombosis was observed in 31(73.8%) patients, arterial thrombosis in 13(31%), peripheral arterial aneurysms in 12(286%), haemoptysis in 38 (90.5%), and fatal haemoptysis in 8(19 %) patients. CTPA revealed: in situ thrombosis in 14(33.3%) patients, true stable PAAs in 13(31), true unstable PAAs in 11(26.2%), stable pulmonary artery pseudoaneurysms (PAPs) in 7(16.7%), unstable PAPs in 17(40.5%), the latter were associated with perianeurysmal leaking in 26(61.9%) and bronchial indentation in 19(45.2%).In regression analysis, fatal outcomes were associated with age in years (p=0.035), arterial thrombosis (p=0.025), peripheral arterial aneurysms (p=0.010), intracardiac thrombosis (p=0.026) and positively associated with haemoptysis severity (p